2021
DOI: 10.3389/fonc.2021.688410
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Melanocytic Lesions in Pediatric Patients: Clinical-Pathological Findings and the Diagnostic Value of PRAME

Abstract: Pediatric melanoma is a rare disease especially in children aged younger than 10 years old. Recent estimates report a rise of disease incidence in both adults and children. Diagnostic work-up is challenging in pediatric melanoma, as it displays a wide range of clinical presentations. Immunohistochemical biomarkers have been reported as predictors of malignancy in melanoma, however data specific to pediatric melanoma are poor. Our study aims to contribute to provide evidence of pediatric melanoma clinical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
(20 reference statements)
3
15
1
Order By: Relevance
“…There was only one case considered discordant in which PRAME IHC was 0 but p16 IHC had diffuse weak to moderate p16 staining ( Previous reports revealed the use of PRAME IHC as an effective tool to distinguish benign and atypical melanocytic lesions from malignancy. [11][12][13][14][15][16]22,23,25 The results presented here are consistent with findings from those prior studies. Focusing specifically on spitzoid melanocytic neoplasms, and including much greater numbers of atypical Spitz tumors and spitzoid melanomas than any of the previous studies published to date, the results of the current study found PRAME expression to differentiate histopathologically determined spitzoid melanomas from Spitz nevi and atypical Spitz tumors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…There was only one case considered discordant in which PRAME IHC was 0 but p16 IHC had diffuse weak to moderate p16 staining ( Previous reports revealed the use of PRAME IHC as an effective tool to distinguish benign and atypical melanocytic lesions from malignancy. [11][12][13][14][15][16]22,23,25 The results presented here are consistent with findings from those prior studies. Focusing specifically on spitzoid melanocytic neoplasms, and including much greater numbers of atypical Spitz tumors and spitzoid melanomas than any of the previous studies published to date, the results of the current study found PRAME expression to differentiate histopathologically determined spitzoid melanomas from Spitz nevi and atypical Spitz tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Raghavan et al, 23 focused on the atypical/intermediate category of melanocytic lesions and observed one of two spitzoid melanomas with diffuse PRAME expression. In contrast, Umano et al 25 been no known or documented concerns raised by the patients in our health system for lesional persistence, recurrence, or progression.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this scenario, rising attention is being devoted to this marker, and new studies are being conducted in an attempt to increase experiences, report results, and find safer answers [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%